1973
DOI: 10.1144/gsjgs.129.1.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Gipping Till: a reappraisal of East Anglian glacial stratigraphy

Abstract: The proposed interpretation of Pleistocene stratigraphy, which results from recent 6-inch geological surveys in the Chelmsford and Norwich areas is at variance with generally accepted correlations relating to the drift deposits of East Anglia. The evidence for the existence of the Gipping Till and its associated glaciation is critically examined. It is concluded that widespread chalky boulder clay was formed during only one glacial episode. It is also suggested that the Hoxnian and Ipswichian deposits in East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The sediments of northeast Norfolk consist of two distinct lithologies, a chalk-rich Lowestoft Till occurring over chalk bedrock and a sand-rich North Sea Drift occurring over the Crag bedrock (Boulton et al 1984). These tills were deposited by two ice-sheets that penecontemporaneously advanced over the area (Bristow & Cox 1973); the British Eastern ice-sheet which drained eastern Scotland and flowed down the east coast of Britain and the Scandinavian ice-sheet from the east of the North Sea. Ice cover remained over north Norfolk until the late Anglian (Hart & Peglar 1990).…”
Section: B O R Nmentioning
confidence: 99%
“…The sediments of northeast Norfolk consist of two distinct lithologies, a chalk-rich Lowestoft Till occurring over chalk bedrock and a sand-rich North Sea Drift occurring over the Crag bedrock (Boulton et al 1984). These tills were deposited by two ice-sheets that penecontemporaneously advanced over the area (Bristow & Cox 1973); the British Eastern ice-sheet which drained eastern Scotland and flowed down the east coast of Britain and the Scandinavian ice-sheet from the east of the North Sea. Ice cover remained over north Norfolk until the late Anglian (Hart & Peglar 1990).…”
Section: B O R Nmentioning
confidence: 99%
“…Termed the Wolstonian, with a type locality at Wolston, east of Coventry, this was a late substitute for the ‘Gippingian glaciation’ that had been identified in the Gipping Valley near Ipswich, Suffolk. The substitution arose because research that was in the process of publication showed the ‘Gipping Till’ to be inseparable from the Anglian Lowestoft Till (Bristow and Cox, ; see also the published discussion of that paper). Previously there had been widespread agreement, as the multiple glaciations paradigm had replaced monoglacialism (cf.…”
Section: Introductionmentioning
confidence: 99%
“…1a), and were correlated with the Elsterian and Saalian glaciations of northwest Europe respectively (Mitchell et al, 1973). The view of two Middle Pleistocene lowland glaciations persisted in Britain until deposits relating to the Wolstonian Glaciation in the English Midlands (Shotton, 1986) and northern East Anglia (Baden-Powell, 1948;West and Donner, 1956;Bristow and Cox, 1973;West, 1977, Straw, 1983 were subsequently re-interpreted as Anglian in age (Perrin et al, 1979;Rose, 1987Rose, , 1989Rose, , 1991. As a result, the concept of the Wolstonian Glaciation in Britain was abandoned leaving the Anglian glaciation as the only extensive Middle Pleistocene glaciation.…”
Section: Introductionmentioning
confidence: 99%